Increased Sensitivity of Global Vegetation Productivity to Drought Over the Recent Three Decades. Issue 7 (4th April 2023) - Wei, Xiaonan; He, Wei; Zhou, Yanlian; Cheng, Nuo; Xiao, Jingfeng; Bi, Wenjun; Liu, Yibo; Sun, Shanlei; Ju, Weimin
Abstract: Intensified droughts have been weakening global vegetation productivity, yet how the sensitivity of vegetation productivity to drought changes over time is not well known. Here, using the simulated long‐term gross primary production (GPP) with an improved two‐leaf light use efficiency model and the Standardized Precipitation Evapotranspiration Index (SPEI), we studied the sensitivity of global vegetation productivity to drought, quantified by the corresponding time scale of SPEI with strongest drought impact on GPP, and analyzed the changes in the sensitivity over two time periods (1993–2005 and 2006–2018). Compared to the first period, droughts were more widespread and severer around the world in the second period, as evidenced by increased drought range (increased by 4.43%) and intensity (SPEI03 decreased by 103%). Globally, the area with significant correlation between GPP and SPEI increased by 25.53%, the impact intensity increased by 14.75%, and the drought sensitivity of GPP enhanced by 13.76%; the changing directions were pretty similar across various vegetation types, mostly showing an increasing trend. Moreover, the vegetation in regions with consistently decreasing moisture was affected by drought most strongly and experienced the greatest change in the sensitivity of GPP to drought (enhanced by 10.99%), indicating that the arid and semi‐arid ecosystems should be considered as a research priority in the future. Our results reveal strengthened drought sensitivity of global vegetation productivity in recent decades across various ecosystems and climate transition regions, which could improve our understanding on the behavior and fate of terrestrial ecosystems in the changing climate. Plain Language Summary: Drought is one of the key factors that weaken vegetation productivity, but there is a lack of research on the changes in vegetation sensitivity to drought at the global scale. Based on long‐term gross primary productivity (GPP) simulated with an improved two‐leaf light use efficiency model and the standardized precipitation evapotranspiration index (SPEI), we studied the changes in vegetation GPP sensitivity to drought by comparing the time scale of SPEI with strongest impact of drought on GPP over two time periods (1993–2005 and 2006–2018). The extent, intensity, and frequency of droughts have increased in the last three decades. Globally, the area and intensity of drought effect on vegetation increased and the sensitivity of GPP to drought enhanced, occurring in most vegetation types. In addition, the increase in vegetation sensitivity to drought was the strongest in regions with persistent decreasing moisture, implying the need to focus on the impacts of drought on arid and semi‐arid ecosystems. This study can deepen our insights into the response of vegetation to climate change. Key Points: Droughts have become more widespread and severer around the world during the recent decades Drought sensitivity of vegetation gross primary productivity was enhanced globally and across most vegetation types The sensitivity increased most strongly in the regions with persistently decreasing water availability